2020
DOI: 10.1007/s12410-020-9535-z
|View full text |Cite
|
Sign up to set email alerts
|

CMR in Pericardial Diseases - an Update

Abstract: Purpose of Review To review the latest developments and the current role of the cardiac magnetic resonance (CMR) in pericardial diseases and their complications. Recent Findings Cardiac Magnetic Resonance (CMR) has the ability to incorporate anatomy, physiology, and "virtual histology" strategies to achieve the most accurate diagnosis for even the most demanding, pericardial diseases. Summary Acute, chronic, recurrent, and constrictive pericarditis as well as pericarditis related complications, pericardial mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Myocardial LGE was visually defined by two observers based on the presence and predominant pattern as ischemic or non-ischemic 44 . Pericardial involvement was considered present when enhancement involved both pericardial layers, irrespective of the size of pericardial effusion 46 . Cine images were employed for derivation of GLS analyses using Medis Suite MR version 2.1 (Medis Medical Imaging Systems) 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial LGE was visually defined by two observers based on the presence and predominant pattern as ischemic or non-ischemic 44 . Pericardial involvement was considered present when enhancement involved both pericardial layers, irrespective of the size of pericardial effusion 46 . Cine images were employed for derivation of GLS analyses using Medis Suite MR version 2.1 (Medis Medical Imaging Systems) 47 .…”
Section: Methodsmentioning
confidence: 99%
“…From myocardial studies it is indicated that diseases with myocardial thinning with partial volume effects, such as dilative cardiomyopathy, are important factors leading to changes in parametric mapping values and causing alterations related to structural thickness even without changes in the tissue structure 9 23. Although parametric mapping has increasingly been used for the diagnosis of myocardial diseases, pericardial mapping is still hampered due to the thin nature of the healthy pericardium surrounded by high-intensity epicardial fat and medium-intensity myocardium 24–26. To further assess the clinical value of T1/T2 mapping beyond a convoluted way of measuring structural thickness, those parameters should be evaluated against each other and regressed for.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Native T1 has also the potential of detailed tissue characterization, allowing the distinction between pericardial enhancement and pericardial fat (both positive in LGE sequences). 3 …”
Section: Discussionmentioning
confidence: 99%